PENGARUH STATUS EKONOMI KELUARGA DAN LINGKUNGAN BELAJAR TERHADAP PRESTASI BELAJAR SISWA MATA PELAJARAN IPS DI SMP NEGERI SE KECAMATAN BATU AMPAR KABUPATEN TANAH LAUT - Elly Ermawati (JURNAL SOCIUS, 2014)
The purpose of this study to analyzed Effects of family socioeconomic status and learning environment influence on student achievement in social studies SMP Se District of Batu Ampar Tanah Laut district. The Methodology of this study used a quantitative approach with a regression method or seek influence. Total population in this research consisted of 456 students with a sampling technique using proportional random sampling, sample size of 213 students. Analysis of the data is used descriptive analysis and T test analysis. The results showed that the status of the results of the level of influence of family economic status and learning environment influence on student achievement in social studies SMP Se District of Batu Ampar Tanah Laut district. Then the results from the 0000 level of effect is variable economic status and learning environment on learning achievement. This means that the economic status of the family and the learning environment influence on learning achievements. Based on these results it is suggested parents should be able to give encouragement to their children in order to improve their learning achievement in social studies.Keywords: Family Economic Status, Environmental Learning, Student Achievement